Participação do hormônio alfa-melanócito estimulante na melhora do reparo de feridas pelos efeitos sistêmicos da tolerância oral - Kênia Soares de Souza (2015)
Parenteral injection of a tolerated protein has systemic effects that are able to block immune responses and inflammatory reactions triggered by exposure to unrelated antigens. These effects are not dependent on the presence of the two antigens on the same site and the injection of the tolerated protein may precede the exposure to the second antigen by upto three days. The intraperitoneal injection of tolerated proteins soon before skin injury inhibits the inflammation in the initial phase of healing, resulting in smaller scars and an arrangement of collagen fibers in the neodermis similar to that found in intact skin. The fast and systemic effects of tolerated proteins made us suspect of the involvement ofglucocorticoid, neuropeptide alpha-melanocyte-stimulating-hormone (-MSH), vasoactive intestinal-peptide (VIP) and substance P (SP) in their anti-inflammatory events. Plasma levels of peptides were assayed by immunoenzymatic methods. We found increased plasma levels of -MSH after tolerated antigen injection, but no alteration in VIP and SP. Using immunofluorescence we detected higher expression of -MSH in wounds of mice exposed to the tolerated protein. The effects of i.p. injection of -MSH were similar to those of tolerated antigen i.p. injection, with reduced inflammatory infiltrates, smaller scars and better organization of collagen fibers. Injection of agouti signaling protein, an antagonist of -MSH receptor, blocked the anti-inflammatory effects of the tolerated protein. These results indicate that -MSH takes part in the anti-inflammatory and healing effects of the tolerated protein.